The scourge between stars - Brown, Ness (Nightfire, Tor Publishing Group, 2023)
"A tense, claustrophobic sci-fi/horror blend set aboard a doomed generation ship harboring something terrible within its walls. As acting captain of the starship Calypso, Jacklyn Albright is responsible for keeping the last of humanity alive as they limp back to Earth from their forebears' failed colony on a distant planet. Faced with constant threats of starvation and destruction in the treacherous minefield of interstellar space, Jacklyn's crew has reached their breaking point. As unrest begins to spread throughout the ship's Wards, a new threat emerges, picking off crew members in grim, bloody fashion. Jacklyn and her team must hunt down the ship's unknown intruder if they have any hope of making it back to their solar system alive"--